MANAJEMEN STRATEGIS PENDIDIKAN ISLAM: MEMBANGUN KEBERLANJUTAN PENDIDIKAN MELALUI TRANSFORMASI DIGITAL DAN NILAI-NILAI KEISLAMAN DI TENGAH TANTANGAN GLOBAL (STUDI KOMPARATIF SMP AL AZHAR 1 BANDAR LAMPUNG DAN SMP ADAB KUSUMA BANGSA NATAR) - Agung Safitri; Yusuf Effendi; Fadhilla Washilla; Tin Amalia Fitri; Amiruddin (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study analyzes the strategic management of Islamic education in facing digital transformation and global sustainability challenges through a comparative study at two Islamic junior high schools in Lampung Province: SMP Al Azhar 1 Bandar Lampung and SMP Adab Kusuma Bangsa Natar. A qualitative descriptive-comparative approach was applied through interviews, observations, and document analysis. Preliminary findings indicate that sustainable Islamic digital education rests on three key dimensions: technology transformation as worship, ethical-spiritual governance, and faith-based leadership resilience. SMP Al Azhar 1 emphasizes structured digital management through LMS and cloud systems, while SMP Adab Kusuma Bangsa focuses on digital-adab culture and social collaboration. This study introduces a new conceptual framework, the Islamic Digital Sustainability Framework (IDSF), integrating digital transformation theory (Al-Kandari et al., 2024) and maqasid al-shariah (Rahman & Hassan, 2023) to guide sustainable strategic management in Indonesian Islamic schools.